The Talking Stick Model Improves Mathematics Learning Outcomes for Fourth Grade Elementary School Students - Shegefandini, Mutiara; Sari, Elok Fariha (International Journal of Elementary Education, 2024)
The problem that often occurs is that studying mathematics in elementary school seems boring, resulting in low learning outcomes. This research aims to analyze the application of the Talking Stick learning model to improve mathematics learning outcomes in fourth-grade elementary school students. This type of research is quantitative research. This research uses a non-equivalent control group essay method with a quasy-experimental type. The subjects of this research were 27 grade IV elementary school students, consisting of 13 male students and 14 female students. The data collection methods used in this research are observation, interviews, tests and observation sheets. The instruments used to collect data were observation sheets and test questions. The techniques used to analyze the data are qualitative descriptive analysis techniques and quantitative and inferential statistics. The research results show that applying the Talking Stick learning model, which pays attention to the number of members in each group, can improve the mathematics learning outcomes of fourth-grade elementary school students. In the initial test, six students (22%) got a score of 76; in the previous pretest results of the application of Talking Stick learning, there were nine students (33%). After the implementation of Talking Stick learning, 26 students out of the total got scores above the KKM. The t-test results also show differences in mathematics learning outcomes after implementing the Talking Stick learning model. It was concluded that the Talking Stick learning model can be used in mathematics learning.